Essentials of contemporary management - Jones Gareth R. (McGraw-Hill, 2007)
In this ninth edition of Essentials of Contemporary Management, we continue to focus on providing the most up-to-date account of the changes taking place in the world of management and management practices while maintaining our emphasis on making our text relevant and interesting to students. And we know from feedback from instructors and students that the text does engage them. Our increased focus on the challenges and opportunities facing businesses large and small and integrated timely examples bring management issues to life for students. The number and complexity of strategic, organizational, and human resource challenges facing managers and employees continue to rise. In most companies, managers at all levels address these challenges by implementing new and improved management techniques and practices. Today, relatively small differences in performance between companies, such as in the speed at which they bring new products or services to market or in the ways they motivate their employees to find ways to reduce costs or improve performance, can combine to give a company a significant competitive advantage. Managers and companies that utilize proven management techniques and practices in their decision making and actions increase their effectiveness over time"-- Provided by publisher